Direct bulk-sensitive probe of 5f symmetry in URu2Si2 - Sundermann, Martin; Haverkort, Maurits W. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The second-order phase transition into a hidden order phase in URu2Si2 goes along with an order parameter that is still a mystery, despite 30 years of research. However, it is understood that the symmetry of the order parameter must be related to the symmetry of the low-lying local electronic fff-states. Here, we present results of a spectroscopic technique, namely core-level nonresonant inelastic X-ray scattering (NIXS). This method allows for the measurement of local high-multipole excitations and is bulk-sensitive. The observed anisotropy of the scattering function unambiguously shows that the 5fff ground-state wave function is composed mainly of the Γ1Γ1Γ1 with majority JzJzJz = |4⟩|4⟩|4⟩ + |−4⟩|−4⟩|−4⟩ and/or Γ2Γ2Γ2 singlet states. The incomplete dichroism indicates the possibility that quantum states of other irreducible representation are mixed into the ground state.
Gesehen am 26.05.2020